1981
DOI: 10.1159/000481016
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Alpha-Adrenergic Receptors in Newborn Platelets: Cause of Abnormal Response to Epinephrine

Abstract: Platelets of newborn infants fail to aggregate or release adenosine diphosphate in response to epinephrine. Because epinephrine-induced aggregation is an α-adrenergic event, we considered the possibility that newborn platelets possess fewer α-adrenergic receptors than do those of adults. Therefore we compared the specific binding of the α-adrenergic antagonist, [3H]-dihydroergocryptine (DHE), in intact washed platelets prepared from paired samples of maternal and cord platelet-rich plasma. Newborn platelets de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 2 publications
3
42
0
Order By: Relevance
“…Using this technique hyporeactivity of neonatal compared to adult platelets after in vitro stimulation with various agonists was demonstrated. This was consistent with the earlier reports [3,6,14,24] of poor platelet aggregation response. Another study utilising¯ow cytometry [12] reported that neonates of very low birth weight do not have circulating activated platelets and that compared to adults their platelets are markedly hyporeactive to various agonists (thrombin, ADP, epinephrine, and U 46619) in the physiological milieu of whole blood.…”
Section: Introductionsupporting
confidence: 94%
See 1 more Smart Citation
“…Using this technique hyporeactivity of neonatal compared to adult platelets after in vitro stimulation with various agonists was demonstrated. This was consistent with the earlier reports [3,6,14,24] of poor platelet aggregation response. Another study utilising¯ow cytometry [12] reported that neonates of very low birth weight do not have circulating activated platelets and that compared to adults their platelets are markedly hyporeactive to various agonists (thrombin, ADP, epinephrine, and U 46619) in the physiological milieu of whole blood.…”
Section: Introductionsupporting
confidence: 94%
“…Platelet function in neonates is dicult to investigate by conventional methods because of the large amount of blood required. Results are con¯icting, most studies using conventional aggregation methods [3,6,14,24] have shown a diminished response to various agonists: platelets of newborns exhibited a low response when induced by collagen and adenosine diphosphate (ADP) [6]; normalization of platelet aggregation response was beginning by the 5th day of life [23]. Platelet aggregation [18] with platelet-rich plasma was markedly impaired in neonatal blood when platelets were stimulated with ADP, epinephrine, collagen, or thrombin, while aggregation with whole blood showed no dierences between neonates and their mothers when ADP and collagen were used as the stimulating agents.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation response of neonatal platelets to thrombin and arachidonic acid is similar to that of adult platelets whereas aggregation to epinephrine is reduced due to decreased alpha-adrenergic receptors on neonatal platelets [2,18]. Neonatal platelet aggregation to collagen is markedly decreased although the major platelet collagen receptor, GPIa-IIa, is present in adult concentrations.…”
Section: Physiology Of Neonatal Plateletsmentioning
confidence: 95%
“…Initial platelet aggregation using flow cytometry consistently demonstrated that platelets from neonatal cord blood were less responsive than adult platelets to agonists such as adenosine 5’diphosphate, epinephrine, collagen, thrombin and thromboxane analogs [31]. The mechanism(s) underlying these differences are still poorly understood, although it has been suggested that the hyporesponsiveness to epinephrine is probably due to the presence of fewer α2-adrenergic receptors [32]. In addition, the reduced response to collagen likely reflects the impairment of calcium mobilization [33], and the decreased response to thromboxane may result from differences in signaling downstream from the receptor in neonatal platelets [34].…”
Section: Differences Between the Adult And Pediatric Hemostatic Systemsmentioning
confidence: 99%